Chitosan oligosaccharide modified liposomes enhance lung cancer delivery of paclitaxel - Miao Yun-qiu; Chen Ming-shu; Zhou Xin; Guo Lin-miao; Zhu Jing-jing; Wang Rui; Zhang Xin-xin; Gan Yong (Acta Pharmacologica Sinica, 2021)
Lung cancer is one of the leading causes of cancer-related death worldwide. Various therapeutic failed in the effective treatment of the lung cancer due to their limited accumulation and exposure in tumors. In order to promote the chemotherapeutics delivery to lung tumor, we introduced chitosan oligosaccharide (CSO) modification on the liposomes. CSO conjugated Pluronic P123 polymers with different CSO grafting amounts, called as CP50 and CP20, were synthesized and used to prepare CSO modified liposomes (CP50-LSs and CP20-LSs). CP50-LSs and CP20-LSs displayed significantly enhanced cellular uptake in A549 cells in vitro as well as superior tumor accumulation in vivo compared with non-CSO modified liposomes (P-LSs). This phenomenon was related to the increased affinity between CSO modified liposomes and tumor cells following massive adsorption of collagen, which was highly expressed in lung tumors. In the A549 tumor-bearing mouse model, intravenous injection of paclitaxel (PTX)-loaded CP50-LSs every 3 days for 21 days resulted in optimal antitumor therapeutic performance with an inhibition rate of 86.4%. These results reveal that CSO modification provides promising applicability for nanomedicine design in the lung cancer treatment.